EFEKTIFITAS PELAYANAN PUBLIK PADA LAYANAN KARTU TANDA PENDUDUK YANG TERPADU (KADO TERINDAH) DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SUKABUMI - Tuah Nur; Detio fikri firjani; Nopia, Nopia; Salma Salsabila Saumi (JRPA - Journal of Regional Public Administration, 2023)
Public services are all activities in the framework of fulfilling basic needs in accordance with the basic rights of every citizen and resident over an item, in this article describes the effectiveness of public services in the Application for making identity cards at the Sukabumi City population and civil registration service, e-KTP is a government product that must be owned by all Indonesian people in accordance with Article 63 of this Law confirms, residents of Indonesian Citizens and Foreigners who have a Permanent Stay Permit who are 17 (seventeen) years old or have been married or have been married are required to have Electronic KTP (e-KTP), of course, at a free price and also excellent service provided by the local Population and Civil Registration Service. The presence of the concept of e-government (electronic government) is an answer in facing the current era of digitalization. various kinds of problem phenomena such as (1) Timeliness of service (2) It is still unclear about socialization of the community about the application Kado Terindah (3) Facilities and Infrastructure.